Old but gold? Examining the effect of age bias in reward-based crowdfunding - Seigner, Benedikt David Christian; McKenny, Aaron F.; Reetz, David K. (Journal of Business Venturing, 2024)
While age is positively related to entrepreneurial success, the prevailing stereotype favors younger entrepreneurs. To better understand how these contradictory perspectives influence funding decisions, we examine the role of age in a sample of 41,602 reward-based crowdfunding campaigns from Indiegogo. We find a negative correlation between an entrepreneur's apparent age and funding performance, indicating a preference for younger entrepreneurs. However, we also find age-based homophily where older entrepreneurs' campaigns attract older backers. Our study distinguishes between statistical and status-based discrimination to understand the multi-faceted nature of age in reward-based crowdfunding and demonstrate how investment motives mitigate and reinforce age-based discrimination.